GENDER ROLES IN OFF-FARM INCOME GENERATING ACTIVITIES AMONG YOUTHS IN RURAL ENUGU STATE, NIGERIA - Obetta, Angela E.; Igwe, Angela C.; Onyishi, Charity, N.; Nzennwa, Rosemary C.; Ogbu, Julieth A. (African Journal of Social and Behavioural Sciences, 2025)
Nigeria is predominantly rural, with high poverty levels and a populace primarily engaged in agriculture. However, agriculture alone cannot alleviate poverty due to its seasonality. This study analyzed gender differences in youth engagement in off-farm income-generating activities in rural areas of Enugu State, Nigeria. A multistage random sampling technique was used to select 360 respondents. Data were collected using semi- structured questionnaires and analyzed with descriptive and inferential statistics, including a logit regression model. The results showed a deviation from conventional agricultural means of livelihood among youths, with 98.3% engaged in off-farm activities. Key activities included wage-earning in civil service (31.9%), artisan work (12.8%), and customer service (12.8%). Significant gender differences were observed: males contributed an average of ₦72,800.00, while females contributed ₦54,108.10. Motivating factors for engagement included income diversification, financial risk mitigation (33.9%), and access to new skills (24.4%). Barriers included lack of access to resources such as land and capital (35.3%), cultural norms (30.6%), and gender-specific constraints like childcare responsibilities (16.1%). Higher educational attainment and income levels positively influence youth participation in off-farm activities, emphasizing the role of socio-economic empowerment. Based on the findings, the study recommends the development and implementation of policies and programs that address the gender disparities observed in off-farm income generation. This could include initiatives aimed at providing equal access to resources such as land, capital, and technology for both male and female youths. Additionally, gender-sensitive training programs and mentorship opportunities can help empower young women to overcome barriers and actively participate in off-farm economic activities.